The Role of Religious Tourism in Religious Moderation: A Case Study on Hindu Places of Worship in North Sumatra - Efni Safitri, Lies Utami (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study examines the impact of religious tourism, particularly in Hindu places of worship in North Sumatra, on religious practices and levels of religious moderation among adherents, especially non-Hindus. Religious tourism is increasingly popular globally, including in Medan, Indonesia. This study aims to analyze how religious tourism influences religious practices and levels of moderation among adherents, specifically non-Hindus in the area. Participation in religious tourism can influence the process of religious moderation, whereby tourists' experiences at places of worship can open their minds to a more inclusive and tolerant understanding of religious diversity. This can foster the development of moderate attitudes in religious practices and interfaith interactions. Non-Hindu adherents who visit have the opportunity to expand their symbolic understanding of Hinduism, thereby promoting tolerance and better understanding. The results of this study have significant implications for promoting religious moderation and interfaith harmony in Indonesia. This article suggests that religious tourism can be used to enhance interfaith dialogue and support efforts toward religious moderation in various religious communities. These implications can assist policymakers and religious practitioners in designing more inclusive and supportive programs and policies to build a more tolerant and moderately religious society.